Zero field magnetisation like a function of temperature vanished in ##T=T_c## as ##(T_c-T)^{\beta}##. Let ##M_1## be a magnetisation for temperature ##T_1##. Since ##\forall M<M_1##, ##(\frac{\partial A}{\partial M})_T=H=0## it follows that(adsbygoogle = window.adsbygoogle || []).push({});

[tex]A(T_1,M)=A(T_1,0)[/tex] for ##M \leq M_1(T_1)##

Why only for ##M \leq M_1(T_1)##?

Now define the function

[tex]A^{*}(T,M)=\{A(T,M)-A_c\}+(T-T_c)S_c[/tex]

[tex]S^{*}(T,M)=S(T,M)-S_c[/tex]

So ##S^{*}(T,M)=-(\frac{\partial A^{*}}{\partial T})_M##

Now in Griffiths construction I need to drive a tangent in point ##T=T_1##. Eq of tangent is

[tex]f(T)=A^{*}(T_1,M_1)+(T-T_1)(\frac{\partial A^{*}}{\partial T})_{T=T_1}[/tex]

I can't visualise this.

**Physics Forums - The Fusion of Science and Community**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# The Griffiths inequality

Can you offer guidance or do you also need help?

Draft saved
Draft deleted

**Physics Forums - The Fusion of Science and Community**